2013
DOI: 10.1097/tp.0b013e318276a1c8
|View full text |Cite
|
Sign up to set email alerts
|

Fast Detection of Renal Ischemia in Transplanted Kidneys With Delayed Graft Function—An Experimental Study

Abstract: Microdialysis provided an early warning of arterial occlusion in transplanted grafts with delayed graft function. It may become a valuable tool for postoperative monitoring and detection of thrombosis after renal transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Approximately 50-70% of the mortality occurs in ARF patients in intensive care who require dialysis and among postoperative patients, 25-100% of them suffer from ARF. Regarding renal transplantation, renal IRI may elicit acute posttransplant tubular necrosis [85][86][87][88] and delayed graft function [89,90]. Reperfusion provokes inflammation by the activation of enzymes and chemical mediators, such as prostaglandins, leukotrienes, lysozymes, phospholipase A2, and ROS, in renal IRI.…”
Section: Renal Irimentioning
confidence: 99%
“…Approximately 50-70% of the mortality occurs in ARF patients in intensive care who require dialysis and among postoperative patients, 25-100% of them suffer from ARF. Regarding renal transplantation, renal IRI may elicit acute posttransplant tubular necrosis [85][86][87][88] and delayed graft function [89,90]. Reperfusion provokes inflammation by the activation of enzymes and chemical mediators, such as prostaglandins, leukotrienes, lysozymes, phospholipase A2, and ROS, in renal IRI.…”
Section: Renal Irimentioning
confidence: 99%
“…The mortality rate of ARF remains between 50% and 70% among patients who receive intensive care who require dialysis and ranges between 25% and 100% in postoperative patients suffering from ARF. Renal IRI is unavoidable in renal transplantation and may lead to acute posttransplant tubular necrosis (21,24,49,55) and delayed graft function (27,47). Recent findings have indicated that carbon monoxide (CO), an endogenous byproduct of heme degradation through the heme oxygenase (HO) system, exerts cytoprotective effects by reducing the expression of proinflammatory mediators, preventing vascular constriction, decreasing platelet aggregation, and inhibiting apoptosis (41, 66).…”
mentioning
confidence: 99%
“…Blood samples were analyzed for creatinine, while urinary samples were analyzed for creatinine, protein and N -acetyl-β- d -glucosaminidase (NAGase) activity as described previously [ 13 ]. Urinary levels of neutrophil gelatinase-associated lipocalin (NGAL) were determined using a commercially available enzyme-linked immunosorbent assay kit (BioPorto Diagnostics A/S, Gentofte, Denmark) [ 22 ]. NGAL and NAGase are both markers of tubular injury.…”
Section: Methodsmentioning
confidence: 99%